Modelos biométricos aplicados ao melhoramento genético de trigo duplo propósito - Carvalho, Ivan Ricardo (2015)
The dual purpose wheat has the capacity to produce forage and grain, through the expression of morphological and bromatologic traits and yield components. Thus, the overall goal was to identify biometric models to understand the interrelationships between traits, direct and indirect selection in breeding wheat for dual purposes. The specific objectives of this study were to determine the canonical correlations between groups of morphological traits and grain yield, and identify the direction and the magnitude of the relationship; and identify the phenotypic relationships of cause and effect bromatologic between forage characters in wheat genotypes under different dual purpose cutting managements. The experiments were conducted in the growing seasons 2013 and 2014 in the experimental area of the Federal University of Santa Maria Campus Frederico Westphalen - RS. A randomized complete block design was used in three trials, the first experiment was arranged in a factorial: five genotypes (BRS Tarumã, BRS Umbu, BRS Figueira, BRS Guatambu and BRS 277) x four cutting managements (uncut, a cut, two cuts and three cuts). The second experiment was arranged in a factorial: Five genotypes (BRS Tarumã, BRS Umbu, BRS Figueira, BRS Guatambu and BRS 277) x Three cutting managements (first cut, second cut and third cut). The traits evaluated were: number of tillers per plant (AF), stem diameter of tillers (DAF), diameter of the main stem (DCP), number of fertile tillers (AFF), number of ears per square meter (ESPM), number of grains per ear (NGE), grain weight per ear (MGE), thousand grain weight (MMG), grain yield (RG), weight hectolitre (PH), green matter per hectare (MV), dry matter per hectare (MS), percentage of hemicellulose (HEM), cellulose (CEL), mineral matter (MM), neutral detergent fiber (FDN), acid detergent fiber (FDA), lignin (LIG), total carbohydrates (CT), carbohydrates no fiber carbohydrates (CNF), crude protein (PTN), and lipids (LIP). Groups of morphological traits and grain yield in wheat dual purpose reveal highly significant relationships. In the management at uncut and one cut wheat, associations are similarly established for both groups, by increasing the DCP, and determining the ESPM the increase, NGE and MGE, MMG, PH and RG. With two cuts the associations are established through the DAF, which influences an increase in MMG, PH and RG. Three cuts showed that the increase in AF increment the ESPM, NGE and MGE, MMG, PH and RG. The indirect selection aimed at increasing the PTN in the first cut can be based on CT, CNF and MV. The second cut provides indirect selection with LIG, CNF, MV and MS. The increase of PTN in the third cut can be obtained by indirect selection to the FDA, CEL, LIG, MM, MV and MS. Indirect selection through forage characters and bromatologic can be successful, since it considers the effect assigned to each cutting management.